Efforts To Improve Student Learning Activities Using The Students Activity Sheet In Class IX-2 SMPN 32 Padang - Doris Yelniwetis; Qadriati Qadriati; Ramli Ramli; Mitra Miswarni; Yurnita Yurnita (Bioeducation Journal, 2018)
Science is an important field of study to support science and technology. Many efforts have been made to improve the quality of education such as curriculum change, teacher competency improvement to stimulate student activities and the provision of learning resources. One that can be implemented to improve the quality of education through increased student activity is to multiply the source of learning such as LKS. This study aims to determine the increase in student learning activities using student activity sheets on IX-2 class IX-2 SMPN 32 Padang. Research includes classroom action research. From the data analysis, it can be concluded that there is an increase of student activity on the subject of Science class VII SMPN 32 Padang using Student Activity Sheet.